NUMERICAL ANALYSIS OF SHALLOW FOUNDATIONS ON PURELY COHESIVE SOIL UNDER ECCENTRIC LOADING - KHITAS, N. E. H; BENMEDDOUR, D; MELLAS, M; MABROUKI, A (Courrier du Savoir, 2016)
The classical theory of the bearing capacity of shallow foundations is based on the effective width approach for the case of vertical eccentric loading. This method stipulates that the area of the foundation, used in the calculation of the bearing capacity, is equal to the area of a fictive foundation on which the loading is applied at the center. This paper evaluates the performance of this approach in predicting the ultimate load of the footing. A numerical analysis is performed to estimate the undrained bearing capacity mobilized in a purely cohesive soil under a strip footing, using the finite difference code FLAC3D (Fast Lagrangian Analysis of Continua in 3 dimensions). The results of this analysis show that the effective width approach provides a good approximation of the bearing capacity for this kind of problems.